2002
DOI: 10.1037/0022-0167.49.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment orientations and college student distress: Test of a mediational model.

Abstract: A model for predicting college student distress that included measures of negative life event impacts, adult attachment orientations, and several indexes of self-organization was tested. Results demonstrated that, controlling for age and negative life impacts, attachment anxiety along with 2 self-organizing predictors (self-splitting, self-concealment) each made unique contributions and collectively explained nearly half of the variance in student distress. In addition, self-splitting and self-concealment effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
89
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 51 publications
9
89
1
Order By: Relevance
“…In addition, Lopez et al (2001Lopez et al ( , 2002 reported that attachment avoidance failed to significantly predict distress after attachment anxiety was controlled for. These findings are consistent with observations that persons with attachment avoidance tend not to acknowledge their distress (Collins, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lopez et al (2001Lopez et al ( , 2002 reported that attachment avoidance failed to significantly predict distress after attachment anxiety was controlled for. These findings are consistent with observations that persons with attachment avoidance tend not to acknowledge their distress (Collins, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several ineffective strategies (e.g., self-concealment or maladaptive perfectionism) were found in previous research to be negative mediators between attachment and distress (e.g., Lopez et al, 2002;Wei et al, 2004). It is possible that (a) insecure attachment is positively associated with the use of these ineffective strategies, (b) these ineffective strategies contribute to basic psychological needs dissatisfaction, and (c) this process contributes to distress.…”
mentioning
confidence: 94%
“…In addition to the above direct associations between attachment and distress, researchers have begun to explore the indirect effects (e.g., mediation effects) beyond these direct associations. To date, studies have identified several mediators of the relationship between attachment and distress such as dysfunctional attitudes and low self-esteem (Roberts, Gotlib, & Kassel, 1996), ineffective coping (Lopez et al, 2001;Wei et al, 2003), self-splitting and self-concealment (Lopez et al, 2002), maladaptive perfectionism (Wei et al, 2004), social competencies and emotional awareness (Mallinckrodt & Wei, 2005), and emotional reactivity and emotional cutoff .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These mediators include low self-esteem (Roberts et al, 1996), problem-solving/coping styles or perceived coping effectiveness (Lopez, Mauricio, Gormley, Simko, & Berger, 2001;Wei et al, 2003), self-splitting and self-concealment (Lopez, Mitchell, & Gormley, 2002), social self-efficacy and emotional awareness (Mallinckrodt & Wei, 2005), maladaptive perfectionism (Wei et al, 2004), and emotional reactivity (i.e., finding it difficult to remain calm when experiencing intense emotions) or emotional cutoff or closure (i.e., pulling away when one is experiencing intense emotions; Wei, Vogel, Ku, & Zakalik, 2005). One limitation of these studies is the use of cross-sectional research designs in which all of the measures were assessed at the same point in time, which limits our ability to draw causal inferences from the findings.…”
mentioning
confidence: 99%